2010
DOI: 10.1086/648729
|View full text |Cite
|
Sign up to set email alerts
|

Improved Virological Outcomes in British Columbia Concomitant with Decreasing Incidence of HIV Type 1 Drug Resistance Detection

Abstract: Background There have been limited studies evaluating temporal changes in the incidence of detection of drug resistance among human immunodeficiency virus type 1 (HIV-1) isolates and concomitant changes in plasma HIV load for treated individuals in a population-wide setting. Methods Longitudinal plasma viral load and genotypic resistance data were obtained from patients receiving antiretroviral therapy from the British Columbia Drug Treatment Program from July 1996 through December 2008. A total of 24,652 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
82
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(94 citation statements)
references
References 15 publications
10
82
1
Order By: Relevance
“…Although recent studies with newer ART regimens have suggested high levels of viral suppression in adults, 5,6 adolescents and young adults do not appear to achieve this goal. Recent first-line viral suppression rates after Highly Active Antiretroviral Therapy (HAART) initiation for adolescents in clinical trials report suppression rates as high as 86%.…”
Section: Viral Suppressionmentioning
confidence: 97%
See 1 more Smart Citation
“…Although recent studies with newer ART regimens have suggested high levels of viral suppression in adults, 5,6 adolescents and young adults do not appear to achieve this goal. Recent first-line viral suppression rates after Highly Active Antiretroviral Therapy (HAART) initiation for adolescents in clinical trials report suppression rates as high as 86%.…”
Section: Viral Suppressionmentioning
confidence: 97%
“…[1][2][3] Simpler, more potent, and less toxic regimens have achieved high levels of sustained HIV viral suppression in clinical trials 4 and in clinical practice. 5,6 A large, multinational, randomized controlled trial has demonstrated the efficacy of how early initiation of antiretroviral treatment can decrease HIV transmission. 1 However, several distinct American populations are not yet benefiting from the movement towards earlier ART initiation.…”
mentioning
confidence: 99%
“…These challenges are particularly acute in low-and middle-income countries (LMIC), where access to drug resistance testing is problematic due to limited resources and infrastructure. Currently, the majority of incident cases of clinically relevant HIV drug resistance involve nonnucleotide reverse transcriptase inhibitor (NNRTI) resistance; therefore, novel resistance testing methods for use in LMIC should, at a minimum, target the HIV reverse transcriptase (RT) region (10)(11)(12)(13).…”
mentioning
confidence: 99%
“…Furthermore, these complications seem to be occurring at higher rates than in age-matched control individuals, likely accounting for the fact that survival of HIV patients still does not match that in the uninfected population, 1 even though viral replication can be controlled in the vast majority of patients in care. 5 In addition, clinical observations from clinicians and patients, some of which have prominently appeared in the lay press, 6,7 cite a process of accelerated aging and debility among those with HIV despite effective treatment.…”
Section: Article See P 651mentioning
confidence: 99%